Association between prenatal vitamin use and congenital abnormalities of the genitourinary tract in a developing country (2012)
Objective To determine the association between prenatal multivitamin supplementation and congenital genitourinary tract anomalies in a group of Colombian newborn babies included in the Latin-American surveillance program (ECLAMC). Study design We included all neonates born between January 2004 and August 2007 registered in the ECLAMC database. Maternal prenatal multivitamin use was assessed for 122 newborns with congenital genitourinary tract anomalies and then compared to 271 non-malformed controls. Results 46,850 births were registered and 122 (26/10,000) of them were identified to have a genitourinary tract anomaly. Prenatal multivitamin supplementation during the first, second, and third trimesters of pregnancy was associated with a reduction in the risk of these anomalies: OR 0.16 (0.08–0.31), OR 0.31 (0.19–0.52), and OR 0.38 (0.23–0.63) respectively. Conclusions Maternal prenatal multivitamins may reduce the risk of congenital genitourinary tract anomalies, not only during the first 8 weeks of gestation but also later in pregnancy, in developing countries.